Implementación de un sistema automatizado para mejorar y optimizar el proceso de faenamiento de ganado vacuno para el camal municipal del cantón Salcedo en el periodo 2014 - 2015 - Bastidas Medina, Cristian E. (2015)
This research was conducted at the municipal slaughterhouse of Salcedo Canton, in order to improve the slaughtering process of cattle. First, slaughter processes are analyzed in each word station; after that, the problems submitted in moving cattle are determined by the researchers and the way to solve them, too. In addition, the functionality of the facilities will be analyzed to establish the areas that have the need to improve according to their activity; once the study was performed, the researchers set out, as a result, the implementation of the automatic transport system in the slaughtering process of cattle for improving and optimizing its production process. Through the evaluation realized, a re-engineering of the slaughterhouse is going to be planned which represents the implementation of the automatic transport system in the slaughtering of cattle with animal air transport for most of the process….